2021
DOI: 10.1289/ehp7404
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride in Drinking Water, Diet, and Urine in Relation to Bone Mineral Density and Fracture Incidence in Postmenopausal Women

Abstract: Background: Although randomized controlled trials (RCTs) have demonstrated that high fluoride increases bone mineral density (BMD) and skeletal fragility, observational studies of low-dose chronic exposure through drinking water ( , the maximum recommended by the World Health Organization) have been inconclusive. Objective: We assessed associations of fluoride in urine, and intake via diet and drinking water, with BMD and fracture incidence in postmenopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
1
11
0
3
Order By: Relevance
“…Tap water fluoride predicted UF SG concentration such that every 1 mg/L increase in tap water fluoride is associated with an increase of 0.48 mg/L UF SG after covariate adjustment. The association between tap water fluoride and UF SG was largest for adults and smallest for children, consistent with studies showing that water and other beverages account for approximately 60-78% of dietary fluoride intake among adults, but only 40% of dietary fluoride intake for children 1 to 10 years old [7,40]. Other important sources of fluoride intake in children may include fluoride-containing dental products or foods that are high in fluoride, such as grapes/raisins, shellfish/fish, strained chicken with broth, and processed chicken.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Tap water fluoride predicted UF SG concentration such that every 1 mg/L increase in tap water fluoride is associated with an increase of 0.48 mg/L UF SG after covariate adjustment. The association between tap water fluoride and UF SG was largest for adults and smallest for children, consistent with studies showing that water and other beverages account for approximately 60-78% of dietary fluoride intake among adults, but only 40% of dietary fluoride intake for children 1 to 10 years old [7,40]. Other important sources of fluoride intake in children may include fluoride-containing dental products or foods that are high in fluoride, such as grapes/raisins, shellfish/fish, strained chicken with broth, and processed chicken.…”
Section: Discussionsupporting
confidence: 84%
“…Older women have higher UF SG than men due to increased fluoride release from bone after menopause [45,46], as well as greater tea consumption [47]. These findings are of public health significance given that chronic exposure to fluoride can change the properties of bone and contribute to skeletal fractures [40], especially post-menopause, with increasing bone loss due to reduced steroid production [48]. A prospective cohort study from Sweden reported a 50% increased risk of hip fractures among postmenopausal women who had higher levels of urinary fluoride [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 A new study in Environmental Health Perspectives sheds light on this issue, examining the association of fluoride intake with bone mineral density (BMD) and fracture incidence in postmenopausal women. 5 The study used data from the Swedish Mammography Cohort, part of the Swedish Infrastructure for Medical Population-based Life-course and Environmental Research (SIMPLER) project. When the cohort was established in 1987, women completed a questionnaire about lifestyle and dietary habits, with a follow-up survey in 1997.…”
mentioning
confidence: 99%
“… 3 , 4 A new study in Environmental Health Perspectives sheds light on this issue, examining the association of fluoride intake with bone mineral density (BMD) and fracture incidence in postmenopausal women. 5 …”
mentioning
confidence: 99%